Procurement of less than 8 UIT and procurement management at a national television station - Barrientos Ricra, Ana Yesenia; Amaya Antón, Hubert Antony; Arapa-Apaza, Henry Valentin; Espiritu-Martinez, Antony Paul; Ramirez Charca, Edith Diana; Romero-Carazas, Rafael (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This means that these entities have the option of implementing mechanisms similar to those established in the state procurement regulations to regulate such procurements, however, there are entities that omit such regulations; in this context, the objective of this study was to determine whether the implementation of mechanisms for acquisitions under 8 UIT are a predictive factor for procurement management in a national television station. The study was basic or pure, quantitative, non-experimental and of association; the sample consisted of 41 collaborators belonging to the unit of analysis, in addition, a review of the documentation was conducted, through a checklist, regarding purchases of less than 8 UIT, made during the year 2022. The results of the review showed 89,23 % compliance with the internal rules and a Tau b coefficient of 0,892 and a p-value of 0,000. It is concluded that the implementation of these mechanisms is a relevant predictive factor to improve the management of purchases in the national television station, these findings have important implications in their timely accounting, which will result in decision making and process optimization in the area of acquisitions under 8 UIT and the management of purchases in the national television industry.